The accountant as a “business partner”: Maqasid Al-Shariah perspective - Zakaria, Zamzulaila; Zakaria, Zarina; Abu Bakar, Intan Suryani (Emerald Publishing Limited, 2025)
Purpose – This study aims to discuss the roles of the accountant as a “business partner” who provides “value-added” services to the organisation; “value added” is conceptualised from theMaqasidAl-Shariah perspective.